Avaliação de biomarcadores séricos e suas relações com marcadores de remodelamento cardíaco e da fibrose miocárdica na cardiopatia chagásica crônica - Isabela Cristina Magalhães (2020)
Background: Chronic Chagas cardiomyopathy (CCC) is responsible for the highest morbidity and the worst prognosis for Chagas disease, in addition to being the most fibrous of heart diseases. In Chagas' disease, predicting which factors correlate with disease progression, morbidity and mortality is a challenge. There is a need to have simple, quantitative and economic risk biomarkers, which add additional value to conventional methods, assisting in the diagnosis and prognosis of patients with CCC. Objectives: In this study, we evaluated serum biomarkers - galectin-3 (Gal-3), metalloproteinases (MMP-9 and MMP-2) and their respective inhibitors (TIMP-1 and TIMP-2), C-terminal collagen peptides (PICP and CTXI) and correlated these biomarkers with cardiac remodeling and myocardial fibrosis in CCC 5, through echocardiographic variables (VEd, LVEF and E / e 'ratio). Methods: Blood samples from chagasic patients in the indeterminate form (FCI) and grade 5 chronic Chagas cardiomyopathy (CCC5) and from individuals not infected (NI) by T. cruzi were used. The dosage of the markers was performed by the Luminex ™ Xmap technique and by ELISA using the Quantibody® kit. For correlation analysis, Pearson's correlation coefficient (r) was used where the degree of linear correlation between two quantitative variables was measured. Results: The results showed a higher concentration of MMP-9 between FCI (p <0.001) and CCC5 (p <0.05) compared to NI. For TIMP-1, there was a higher concentration in FCI (p <0.05) and CCC5 (p <0.05) compared to NI. A higher concentration of MMP-2 was found confronting CCC with FCI (p <0.01). Likewise, there was a higher concentration of TIMP-2 in relation to CCC5 with FCI (p <0.001). There was no statistical difference regarding the concentration of PICP and CTXI. As for Gal-3, there was a higher concentration in CCC (n = 50) compared to FCI (n = 61) (p <0.001). The data also demonstrated a positive correlation between MMP-2 and TIMP-2 (r = 0.7283 and p <0.0001) in the CCC5 group, an inversely proportional correlation between Gal-3 and LVEF (r = -0.5961 and p < 0.01) and directly proportional correlation in patients with CCC5 (r = 0.6656 and p <0.01). Conclusion: Thus, our study concluded that among the evaluated molecules, Gal-3 is a potential marker of cardiac remodeling and myocardial fibrosis in CCC 5.